‘Going Above and Beyond: A Comparative Case Study of the Multilevel Organisation of National Political Parties in the EU Polity’: PhD by Gilles Pittoors (Ghent University), supervisor: Bram Wauters - Dupont, Claire (Politics of the Low Countries, 2025)
Scholars have long been pointing to the growing crisis of democracy and democratic institutions: trends in global democratic governance point to a shrinking of high-quality democratic systems, while assessments of established democracies point to challenges around legitimacy, public trust and public engagement in democratic processes. While the European Union is only rarely the focus of specific research in democratic studies, it is no exception to these broader observations.